The role of human resource management practices in responding to COVID-19 crisis: changes, challenges and future directions - Wan, Yee Mei (2023)
Given the disruption caused by the COVID-19 pandemic, most organisations have been put to the test in terms of strategic resilience and workforce management. It has also created enormous challenges to the working population, jeopardising the existence of both people and organisations. The objective of this study is to determine the challenges that HR professionals face as a result of the Covid crisis. Therefore, it is important to evaluate how Covid-19 will affect HR functions such as compensation, talent, training, and development. With the increased uncertainty caused by the pandemic, human resource professionals play a critical role in rethinking organisational policies for transitioning workforce to remote work and preserving social distance to protect present employees. When working in a virtual environment without face-to-face interaction, managing a virtual workforce without sacrificing efficiency can be quite difficult for managers with insufficient experience. The findings from ten in-depth interviews with highly skilled HR experts from various backgrounds and industries are being analysed in this study using a qualitative research method. By obtaining feedback from the participants and analysing prior research on how each HR function handled the pandemic, it is possible to lay the groundwork for a future HR strategy plan in the event that another crisis arises. This study will then go over a few topics that were not covered in the research, such as strategic workforce planning, employee wellbeing, and engagement, which should be regarded an important area of future research in a crisis situation.